Mental health symptom severity and health care utilization in adolescent and young adult cancer survivors. Issue 28 (1st October 2022) - Baclig, Nikita V.; Comulada, W. Scott; Ganz, Patricia A.
Abstract : 229 Background: Adolescent and Young Adult (AYA) cancer survivors experience psychological sequelae, yet causal pathways between AYA cancer, mood disorders, and mental healthcare remain unclear. The 2019 National Health Interview Survey (NHIS) applies the Patient Health Questionnaire-8 item (PHQ8) and Generalized Anxiety Disorder-7 item (GAD7), providing validated evaluation of mental health (MH) in a national sample. We investigated how AYA cancer history affects MH symptoms and MH care utilization. Methods: Descriptive statistics evaluated depression (PHQ8), anxiety (GAD7), use of MH medications, and receipt of psychotherapy in three groups: adults with AYA cancer history, adults with Older Adult (OA) cancer history, and cancer-free adults. Structural Equation Modeling (SEM) was used to estimate cancer survivorship impact on medication use and receipt of therapy (total effects), as well as direct/indirect effects through depression and anxiety (mediated effects). Results: AYA cancer survivors had higher mean PHQ8 (3.64, 2.80, 2.43, p < 0.001) and GAD7 (3.05, 1.90, 2.05, p < 0.001) compared to OA survivors and cancer-free adults. They reported more medication use for MH (24.8%, 21.0%, 15.2%, p < 0.001), and received therapy more often (14.0%, 8.6%, 9.5%, p = 0.001). Total effects models showed AYA survivors were more likely to have received therapy (OR 1.55, 95% CI 1.20-2.00) and to have taken medications (OR 1.84, 95% CI 1.49-2.28) compared to cancer-free adults. Mediated models examined indirect (mediated by MH symptoms) and direct (residual) pathways. All indirect partial paths (regressor to mediator or mediator to outcome) showed large, significant effects (p < 0.001), except for regression of GAD7 on OA survivors. Direct paths showed large, significant effects of AYA and OA survivorship on medication use, but small nonsignificant effects on therapy. Indirect full paths (regressor to outcome through mediators) demonstrated smaller effects than direct pathways, but overall larger effects for AYA survivors than OA survivors. Conclusions: AYA survivors experience worse MH symptoms and are more likely to utilize MH care than OA survivors and cancer-free adults. Effects of cancer survivorship on MH care utilization were mediated through MH symptom severity. Mediated effects were larger for AYA survivors than OA survivors.Regression coefficients for mediated effects SEM. No Cancer AYA Cancer OA Cancer Took Medication Received Therapy N 28108 664 3099 SEM - Direct Took Medication - 0.403▾ 0.439▾ Received Therapy - 0.189 -0.133 SEM - Indirect GAD7 (partial) - 0.394▾ -0.018 0.098▾ 0.095▾ PHQ8 (partial) - 0.372▾ 0.176▾ 0.141▾ 0.102▾ Took Medication (full) - - Mediator: GAD7 - 0.039▾ -0.002▾ - Mediator: PHQ8 - 0.052▾ -0.033▾ Received Therapy (full) - - Mediator: GAD7 - 0.037▾ -0.002▾ - Mediator: PHQ8 - 0.038▾ 0.018▾ ▾: p < 0.05. Full indirect statistical significance based on partial effects.